Modified flaky zinc base material for water-based inorganic zinc silicate coating, preparation method of modified flaky zinc base material, coating and preparation method of coating
By composite modification and controllable ball milling of the sheet zinc base material to form a continuous protective film, the dispersion and corrosion resistance of the sheet zinc base material in aqueous inorganic zinc silicate coating is solved, and the effect of efficient dispersion, corrosion and convenient construction is achieved.
Patent Information
- Application Number
- CN202510633116.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-07-18
AI Technical Summary
In the prior art, the sheet zinc base material has poor dispersion, easy oxidation, and easy settlement in aqueous inorganic zinc silicate coatings, and the process is complicated, making it difficult to meet the needs of high corrosion resistance and construction convenience.
Compound modifiers include film-forming resins, surfactants and co-solvents to modify the flake-shaped zinc base material. Combined with a controlled ball milling process, a continuous protective film is formed, which improves dispersion and storage stability and reduces the risk of active corrosion of zinc.
It realizes efficient dispersion, excellent anticorrosion and construction performance of sheet zinc base material in aqueous inorganic zinc silicate coatings, extends the coating life, reduces zinc resource consumption, and improves the environmental protection and construction adaptability of the coating.
Smart Images

Figure BDA0005405931430000082 
Figure BDA0005405931430000091 
Figure BDA0005405931430000092
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of zinc coatings, and specifically relates to a modified flaky zinc base material for waterborne inorganic zinc silicate coatings, a preparation method thereof, a coating and a preparation method thereof. Background Art
[0002] As one of the main members of heavy-duty anti-corrosion coatings, zinc base paint has excellent anti-corrosion performance and is widely recognized and used. As the main raw material of dacromet coatings, the flaky zinc base material has a coating thickness of 8 - 12 μm and is applied to metal components such as automotive screws and fasteners. Its excellent electrochemical anti-corrosion performance and layered flaky stacking state provide excellent anti-corrosion performance.
[0003] At present, flaky zinc base materials have begun to be studied for use in heavy-duty anti-corrosion coatings, such as epoxy flaky zinc base paint in an oil-based system, alcohol-soluble inorganic flaky zinc powder paint, and water-based systems such as water-based epoxy flaky zinc base paint and spherical-flake mixed zinc base paint. The addition amount of the flaky zinc base material can be reduced to 1 / 3 of the original spherical zinc addition amount, achieving the same excellent anti-corrosion effect, greatly saving the consumption of zinc resources and reducing the cost of the coating. For example, in the prior art CN111253827B "A Scaly Epoxy Olefin-Zinc Primer and Its Preparation Method", the flaky zinc base material is combined with graphene and used in epoxy zinc base paint, improving the salt spray resistance of the zinc-rich primer while reducing the metal zinc content in the non-volatile matter of the primer. In the prior art CN113897091B "A Composite Anti-Settling Agent for Alcohol-Soluble Inorganic Zinc Silicate Paint, Its Preparation Method, and the Zinc Base Material Component of Inorganic Zinc Silicate Paint and Its Preparation Method", the zinc base material is applied in an alcohol-soluble system; in the prior art CN116200096B "An Anti-Corrosion Spreading Water-Based Zinc-Rich Anti-Corrosion Paint and Its Preparation Method", the flaky zinc base material is in a non-aqueous system mixture. The characteristics of less addition amount and excellent anti-corrosion performance of the flaky zinc base material in steel structure anti-corrosion coatings, and the reduction of zinc mist will also reduce the harm to workers' lungs, making it particularly suitable for the protection of steel structures that require welding and cutting.
[0004] Flaky zinc-based materials are currently generally prepared by wet or dry ball milling processes. For flaky zinc-based materials prepared by the wet grinding process, medium- to high-boiling solvent oils are usually used as ball milling solvents to improve the safety of the ball milling process. However, when removing the solvent and drying, the solvent cannot be completely removed, which affects the drying and densification of the paint film, thereby reducing the comprehensive anti-corrosion performance; for flaky zinc-based materials prepared by the dry grinding process, during the process of grinding and powder making, grinding aids such as grinding assistants and lubricating assistants are added to promote the crushing of zinc particles and prevent the adhesion of fragmented fine zinc particles. The flaky powder prepared by this method has a large specific surface area and strong hydrophobicity, and does not require additional removal of the aids, which is suitable for coatings for ambient temperature drying, but it is difficult to wet and disperse in water-based paints. For example, in the prior art CN112143269B "An aqueous inorganic zinc-rich paint and its preparation method", the flaky zinc-based material used is modified by the wet method, with a cumbersome process and a long time. Its purpose is to solve the problems of uneven dispersion, easy sedimentation, easy corrosion, and rapid failure of the zinc-based material in the existing aqueous inorganic zinc-rich paint.
[0005] In the prior art, few flaky zinc-based materials are used in aqueous inorganic zinc silicate paints. Aqueous flaky inorganic zinc silicate paint is an excellent anti-corrosion and environmentally friendly paint. At the same time, aqueous inorganic zinc silicate paint is an aqueous environmentally friendly paint, and the binder used in it is mainly inorganic silicates, etc. Inorganic materials have the advantages of being non-flammable and non-smoking at high temperatures.
[0006] Therefore, it is necessary to develop a flaky zinc-based material for aqueous inorganic zinc silicate paints, which has good dispersibility, excellent anti-corrosion performance, simple process, convenient construction, and long storage period. Summary of the Invention
[0007] In order to solve the above technical problems, the present application provides a modified flaky zinc-based material for aqueous inorganic zinc silicate paints and its preparation method.
[0008] In the first aspect, the present application provides a modified flaky zinc-based material for aqueous inorganic zinc silicate paints, which includes the following components by weight: 96.5 - 99.5 parts of modified flaky zinc-based material; 0.5 - 3.5 parts of composite modifier; the modified flaky zinc-based material is obtained by coating and modifying the raw material flaky zinc-based material with the composite modifier by ball milling; The particle size D50 of the raw material flaky zinc-based material is 15 - 45 μm, the water surface spreading area is 3000 - 4500 cm 2 / g, and the total zinc content is ≥ 96%; the composite modifier includes film-forming resin, surfactant, and cosolvent; The weight ratio of the film-forming resin: surfactant: cosolvent is (1 - 1.7):(0.4 - 1):(0.4 - 1); Optionally, the film-forming resin includes at least one of a modified acrylate emulsion, an acrylic-modified polyurethane emulsion, and an aqueous silicone resin; the surfactant includes at least one of a non-ionic surfactant and a silicone-modified surfactant; the co-solvent includes at least one of isohexylene glycol and ethylene glycol amine; Optionally, the non-ionic surfactant includes at least one of a fatty alcohol polyoxyethylene ether, an alkylphenol polyoxyethylene ether, and a block polyether; the silicone-modified surfactant includes a polysiloxane surfactant.
[0009] In the technical solution of the first aspect, the raw material flaky zinc base material is modified by ball milling with a composite modifier including a film-forming resin, a surfactant, and a co-solvent. The composite modifier improves the dispersibility, storage stability, and mechanical properties of the modified flaky zinc base material through synergistic effects, reduces the risk of active corrosion of zinc, and extends the coating life. Film-forming resins such as modified acrylate emulsions, acrylic-modified polyurethane emulsions, and aqueous silicone resins can form a continuous protective film on the surface of the raw material flaky zinc base material, improving the adhesion between the coating and the substrate and preventing zinc powder from falling off; resin coating can reduce the agglomeration of the modified flaky zinc base material, improve its dispersibility in the aqueous system, and prevent sedimentation. Resin coating can enhance the hydrophobicity and chemical resistance of the paint coating, and synergistically improve the anti-corrosion performance with the cathodic protection of zinc. Non-ionic surfactants or silicone-modified surfactants can improve the compatibility between the modified flaky zinc base material and the aqueous medium and promote uniform dispersion. Surfactant molecules adsorb on the surface of the modified flaky zinc base material to form a hydrophobic layer, reducing oxidation or hydrogen evolution caused by contact with water. Isohexylene glycol and ethylene glycol amine co-solvents can extend the open time of the paint during construction and avoid coating defects (such as cracking) caused by rapid drying; by adjusting the weight ratio of the film-forming resin, surfactant, and co-solvent, the rheological properties of the resin can be adjusted to uniformly coat the zinc flakes during ball milling.
[0010] In the first aspect, a low co-solvent dosage design (accounting for 0.4 - 1 part, <1% in the total formulation) is adopted, and it acts synergistically with the film-forming resin and the surfactant, with an extremely low residue amount; Ball milling can significantly improve the dispersibility of the flaky zinc base material in the paint; ball milling can convert mechanical energy into heat energy, promote the diffusion and volatilization of the co-solvent, and reduce the residue amount of the co-solvent.
[0011] The proportions of the components in the composite modifier have a significant impact on the performance of the modified flaky zinc-based material. The film-forming resin dominates the coating and film formation. When the proportion is too low (<1 part), the coating is incomplete, and the modified flaky zinc-based material is prone to oxidation or agglomeration, resulting in poor mechanical properties of the coating. When the proportion is too high (>1.7 parts), it may affect the conductivity and cathodic protection effect of the modified flaky zinc-based material, and the cost increases. The surfactant improves dispersion and wetting. When the proportion is too low (<0.4 part), the dispersion effect is insufficient, and the zinc powder is prone to agglomeration, affecting the coating uniformity. When the proportion is too high (>1 part), it leads to an increase in foam, affecting the denseness of the coating and even reducing the adhesion. The cosolvent adjusts volatilization and leveling. When the proportion is too low (<0.4 part), the volatilization is too fast, affecting the film-forming quality and resulting in pinholes or shrinkage holes. When the proportion is too high (>1 part), the drying time is too long, affecting the construction efficiency and even leading to a decrease in the initial water resistance of the coating. By adjusting the proportions of the components of the composite modifier, the requirements of different construction scenarios can be met. For example, when the proportion of the film-forming resin is high and the surfactant and cosolvent are relatively less, it is suitable for coatings with high zinc content and high anti-corrosion requirements to ensure sufficient coating of the zinc powder and reduce oxidation; or it is suitable for low-humidity or fast-drying environments, and less cosolvent can avoid slow drying. If the proportions of the surfactant and cosolvent increase and the film-forming resin still dominates, it is suitable for systems with high dispersion requirements (such as high-solid coatings) to prevent the settlement of the zinc-based material; or it is suitable for high-temperature or high-humidity environments, and more cosolvent can delay drying and avoid coating defects; if the coating property, dispersion property and workability are balanced, taking into account anti-corrosion performance, storage stability and construction convenience; it is suitable for conventional climate conditions, with moderate drying speed and leveling property.
[0012] The technical solution of the first aspect solves the pain points of traditional zinc powder being prone to oxidation and poor dispersion through the synergy of the flaky structure of the zinc-based sheet and the coating of the composite modifier; maximizes the anti-corrosion efficiency of high zinc content under the premise of environmental protection; and adapts to the diverse market through parameter fine-tuning.
[0013] For the technical solution of the first aspect, the particle size D50 of the raw material flaky zinc-based material is 15 - 45 μm. The moderate particle size ensures the uniform dispersion of the zinc-based material in the coating, avoiding the problems of agglomeration caused by too fine particles or sedimentation of too coarse particles; it is easier to be coated by the composite modifier during ball milling modification, improving the storage stability. The moderate particle size can form a dense coating, reduce the porosity, and enhance the physical shielding effect. The water spreading area of the raw material flaky zinc-based material is 3000 - 4500 cm 2 / g. The high spreading area is more easily coated by the resin / surfactant. The flaky zinc-based material is more likely to be arranged in parallel than spherical zinc powder, extending the penetration path of the corrosive medium and enhancing the barrier anti-corrosion effect; at the same zinc content, the coverage efficiency of flaky zinc is higher, reducing the coating consumption. The flaky zinc is easily coated by the composite modifier, reducing the ball milling time and energy consumption. The high zinc content has less impurities, reducing side reactions with water (such as gelation, hydrogen generation), extending the shelf life of the coating; it can reduce the filler addition amount, simplify the formulation complexity, and meet environmental protection requirements (such as low heavy metals) at the same time.
[0014] In a second aspect, the present application provides a method for preparing a modified flaky zinc base material for the waterborne inorganic zinc silicate coating described in the first aspect, comprising the following steps: S1: Place 96.5 - 99.5 parts of the raw material flaky zinc base material in a pre-stirring container, and while stirring, spray 0.5 - 3.5 parts of a composite modifier into it through a sprayer until pre-mixed evenly; S2: Add 400 - 800 parts of glass beads to a ball mill, add the material prepared in S1 to the ball mill, and perform ball milling to mix evenly; screen the glass beads to obtain the modified flaky zinc base material.
[0015] In S1, the liquid flow rate of the sprayer is 3 - 10 ml / min; the volume flow rate of the spray gas is 5 - 15 L / min; The diameter of the glass beads in S2 is 3 - 10 mm; the rotation speed of the ball milling in S2 is 150 - 350 r / min; the ball milling time is 2.5 - 4.5 h; the screening is performed using a 40-mesh vibrating screen.
[0016] The technical solution of the second aspect realizes the efficient modification of the flaky zinc base material through the composite modifier coating and the controllable ball milling process. The liquid flow rate of 3 - 10 ml / min and the gas flow rate of 5 - 15 L / min ensure uniform atomization of the modifier; spraying while stirring avoids local overdosage or caking; the proportion of the composite modifier of 0.5 - 3.5 parts can precisely control the thickness of the coating layer. The coating layer blocks the contact of water / oxygen, reduces the risk of "flash rust" during storage and construction, and inhibits zinc oxidation; the co-solvent volatilizes preliminarily during the atomization process of the spraying modification, which can reduce the residue of the co-solvent; the spraying parameters are adjustable to adapt to different viscosity modifiers (such as high-solid-content or low-viscosity systems). Ball milling with glass beads, the mechanical force of ball milling promotes the chemical bonding between the modifier and the zinc flakes, improving the adhesion of the coating layer; gentle ball milling avoids the fragmentation of the zinc flakes and maintains the aspect ratio; after ball milling, the modified flaky zinc base material has excellent dispersion performance, anti-corrosion performance, and construction performance.
[0017] In a third aspect, the present application provides a waterborne inorganic zinc silicate coating. The waterborne inorganic zinc silicate coating includes Coating A and Coating B. Coating A includes 35 - 55 parts of potassium silicate aqueous solution, 1.5 - 3 parts of styrene-acrylic emulsion, 1 - 2 parts of silane coupling agent, 0.5 - 2.0 parts of dispersant, 0.1 - 0.3 parts of defoamer, 0.5 - 1.5 parts of anti-settling agent, and 0.2 - 0.5 parts of leveling agent by weight; Coating B includes 10 - 40 parts of the flaky zinc base material for the waterborne inorganic zinc silicate coating described in any one of claims 1 - 4 or the flaky zinc base material for the waterborne inorganic zinc silicate coating prepared by the preparation method described in any one of claims 5 - 6, 5 - 15 parts of barium sulfate, 3 - 10 parts of ferrophosphorus powder, 5 - 10 parts of talc powder, 3 - 8 parts of mica powder, and 4 - 10 parts of potassium feldspar powder by weight.
[0018] When the waterborne inorganic zinc silicate coating is used, the coating B is added to the coating A and mixed evenly.
[0019] In the technical solution of the third aspect, through the two-component design of coating A and coating B, the organic-inorganic hybrid modified potassium silicate solution, the modified flaky zinc base material and the filler of coating B are compounded, significantly improving the comprehensive performance of the waterborne inorganic zinc silicate coating.
[0020] In the coating A, the modified potassium silicate solution is synergistically modified by styrene-acrylic emulsion and silane coupling agent to form an organic-inorganic hybrid network. The styrene-acrylic emulsion enhances flexibility and adhesion; the silane coupling agent bridges the inorganic potassium silicate and the organic phase, improving compatibility. Using the modified potassium silicate solution can improve the impact resistance and flexibility of the waterborne inorganic zinc silicate coating, enhance the corrosion resistance, and at the same time enhance the hydrolysis resistance of the modified potassium silicate solution, making the waterborne inorganic zinc silicate coating have a long storage period.
[0021] In the coating B, the modified flaky zinc base material with good dispersion and corrosion resistance prepared in the first aspect or the second aspect is used as the base material, combined with barium sulfate to improve the coating hardness and chemical resistance, phosphorus iron powder to assist in passivation and corrosion prevention and reduce the zinc powder dosage, and the characteristics of talc powder / mica powder / potassium feldspar powder to synergistically enhance the physical shielding and leveling property, which can significantly improve the corrosion resistance and construction adaptability of the waterborne inorganic zinc silicate coating.
[0022] The waterborne inorganic zinc silicate coating provided by the third aspect uses the waterborne modified potassium silicate solution as the core film-forming substance, uses the flaky zinc base material for the waterborne inorganic zinc silicate coating as the anti-corrosion main body, the waterborne system, high zinc utilization rate (large spreading area of flaky zinc), and fillers such as phosphorus iron powder reduce the zinc powder dosage, making the waterborne inorganic zinc silicate coating have environmental protection and cost advantages. The two components are mixed during use to avoid the premature reaction and gelation of potassium silicate and zinc.
[0023] In the coating B, a combination of fillers with different densities (barium sulfate 4.3 - 4.5 g / cm 3 , phosphorus iron powder 6.0 - 6.2 g / cm 3 , talc powder 2.7 - 2.8 g / cm 3 , mica powder 2.6 - 2.9 g / cm 3 , potassium feldspar powder 2.5 - 2.6 g / cm 3 ) is used to achieve self-organized gradient distribution during the curing process of the prepared waterborne inorganic zinc silicate coating. High-density fillers (such as phosphorus iron powder) sink rapidly, low-density fillers (such as mica powder) float or suspend; medium-density fillers (talc powder, potassium feldspar powder) evenly fill the intermediate layer, thus forming a dense and functionally layered protective structure. The corrosion resistance and construction adaptability of the waterborne inorganic zinc silicate coating are significantly enhanced.
[0024] Fourth aspect, the present application provides a preparation method of the waterborne inorganic zinc silicate coating described in the third aspect, including the following steps: S1': Prepare Coating A. Take 35 - 55 parts of potassium silicate aqueous solution, add 1.5 - 3 parts of styrene-acrylic emulsion while stirring, and stir evenly; dropwise add 1 - 2 parts of silane coupling agent, and stir evenly; then add 0.5 - 2.0 parts of dispersant, and stir evenly; then add 0.1 - 0.3 parts of defoamer, 0.5 - 1.5 parts of anti-settling agent, and 0.2 - 0.5 parts of leveling agent, and stir and mix evenly; S2': Prepare Coating B. Take 10 - 40 parts of modified flaky zinc base material for waterborne inorganic zinc silicate coating, 5 - 15 parts of barium sulfate, 3 - 10 parts of ferrophosphorus powder, 5 - 10 parts of talc powder, 3 - 8 parts of mica powder, and 4 - 10 parts of potassium feldspar powder, and stir and mix evenly; S3': Stir Coating A at low to medium speed, slowly add Coating B to Coating A, and continue to stir at medium to low speed until evenly mixed after adding.
[0025] The molar ratio of silicon dioxide (SiO₂) to potassium oxide (K₂O) in the potassium silicate aqueous solution in S1' is M2.5 - M3.9, and the content of potassium silicate is 45%.
[0026] The technical solution of the fourth aspect adopts a hybrid modification process of stepwise hybridizing the potassium silicate aqueous solution with styrene-acrylic emulsion and silane coupling agent, and a mixing process of adding materials in stages, at low shear, and controlled speed for Coating A and Coating B, which solves the pain points of traditional waterborne inorganic zinc silicate coatings such as easy gelation, uneven dispersion, and poor construction performance. The prepared waterborne inorganic zinc silicate coating has good dispersion, excellent anti-corrosion performance, simple process, convenient construction, and long storage period.
[0027] The molar ratio of silicon dioxide (SiO₂) to potassium oxide (K₂O) in the potassium silicate aqueous solution is M2.5 - M3.9, the free K₂O in the potassium silicate solution decreases, reducing the risk of pre-reaction with zinc (Coating B), avoiding coating gelation, and extending the storage period. The higher the molar ratio (M) of SiO₂ to K₂O, the larger the proportion of silicon-oxygen chains (-Si-O-Si-) in the potassium silicate solution and the higher the crosslinking density. 2.5 - 3.9 in this scheme belongs to medium to high modulus, balancing the reaction activity and stability. The content of the potassium silicate aqueous solution is 45%, which can improve the film-forming density; with moderate viscosity, it can improve the construction adaptability.
[0028] The potassium silicate solution is stepwise hybrid modified with styrene-acrylic emulsion and silane coupling agent to form an organic-inorganic interpenetrating network. First, potassium silicate forms a core-shell structure with the styrene-acrylic emulsion, and then the silane coupling agent is added dropwise. Through hydrolysis and condensation (Si-OH + K-O-Si → Si-O-Si bond), the two phases are bridged to avoid phase separation caused by direct mixing. After hybrid modification, the viscosity of the potassium silicate solution is moderate, and the waterborne inorganic zinc silicate coating prepared with Coating B has good anti-settling performance. 1.5 - 3 parts of styrene-acrylic emulsion and 1 - 2 parts of silane coupling agent can ensure the balance between the organic phase and the inorganic phase.
[0029] The mechanism of potassium silicate first forming a core-shell structure with the styrene-acrylic emulsion is as follows: 1. Potassium silicate undergoes hydrolysis self-condensation and silane coupling agent undergoes hydrolysis condensation to form oligomeric siloxane chains (≡Si-O-Si≡).
[0030] 2. In the initial dispersion stage, in the potassium silicate aqueous solution with high pH (>11) in potassium silicate (inorganic phase), silicate ions (SiO3 2- ) and oligomeric siloxane chains (≡Si-O-Si≡) are uniformly dispersed through electrostatic repulsion. On the surface of the styrene-acrylate copolymer latex particles in the styrene-acrylic emulsion (organic phase), there are negatively charged (-COO-), which electrostatically repel the silicate ions and are temporarily stably suspended.
[0031] 3. In the core-shell structure formation stage, through electrostatic adsorption and hydrogen bond interaction, under low-speed stirring, K + ions in potassium silicate neutralize part of the negative charge on the surface of the styrene-acrylic emulsion, weaken the electrostatic repulsion, and enable the silicate ions to be adsorbed onto the surface of the latex particles through hydrogen bonds (Si-OH···O=C-). The adsorbed silicate ions further condense under alkaline conditions to form a dense siloxane network shell (Si-O-Si bond), wrapping the styrene-acrylic latex particles (core) to form an "organic core-inorganic shell" structure.
[0032] The mechanism of the bridging action of the silane coupling agent is as follows: The added silane coupling agent hydrolyzes and adsorbs directionally under alkaline conditions. The hydrolyzed Si(OH)3 is preferentially adsorbed onto the inorganic shell of the core-shell structure (Si-OH condenses with Si-OH), and the organic end (such as the epoxy group) faces the styrene-acrylic emulsion. The hydrolysis process is: Si(OCH3)3 + 3H2O → Si(OH)3 + 3CH3OH. The hydrolyzed Si(OH)3 reacts with the inorganic phase to strengthen the crosslinking density of the potassium silicate shell. The reaction process with the inorganic phase is Si(OH)3 + Si-O-K → Si-O-Si + KOH; it reacts with the organic phase, and the epoxy group ring-opens and reacts with the carboxyl group (-COOH) or hydroxyl group (-OH) of the styrene-acrylic emulsion to form covalent bonds. 1.5 - 3 parts of the styrene-acrylic emulsion are provided to provide sufficient organic nuclei to avoid brittleness caused by excessive inorganic phase; 1 - 2 parts of the silane coupling agent are used to ensure that at least 1 - 2 bridging molecules are connected to each core-shell structure to form a continuous interpenetrating network.
[0033] Coating B is slowly added to Coating A to prevent local powder aggregation. After mixing, there are no bubbles or particles, and the waterborne inorganic zinc silicate coating has good dispersibility; the viscosity is moderate, and the construction adaptability is good.
[0034] In summary, this application includes the following beneficial technical effects: 1. This application uses a composite modifier including a film-forming resin, a surfactant, and a co-solvent to modify the raw material flaky zinc base material. The film-forming resin dominates coating and film formation, the surfactant improves dispersion and wetting, and the co-solvent adjusts volatilization and leveling. The composite modifier enhances the dispersion, storage stability, and mechanical properties of the modified flaky zinc base material through synergistic effects, reduces the risk of active corrosion of zinc, and extends the coating life; by adjusting the ratio parameters of the composite modifier, diverse requirements can be met.
[0035] 2. This application realizes the efficient modification of the flaky zinc base material through the synergistic process of composite modifier coating and controllable ball milling. The composite modifier coating uses the modifier atomized spray to coat the raw material flaky zinc base material to ensure uniform atomization of the modifier; glass bead ball milling promotes the chemical bonding between the modifier and the zinc flakes; the modified flaky zinc base material modified by composite modifier coating and ball milling has excellent dispersion performance, anti-corrosion performance, and construction performance.
[0036] 3. This application provides a waterborne inorganic zinc silicate coating and a preparation method thereof based on a modified flaky zinc base material. The coating is designed with two components, namely Component A and Component B, which are mixed during use to avoid the premature reaction and gelation of potassium silicate and zinc, thereby extending the storage time of the coating. Styrene-acrylic emulsion and silane coupling agent are used to synergistically modify the potassium silicate solution to ensure the balance between the organic and inorganic phases, and improve the impact resistance, flexibility, corrosion resistance and storage period of the waterborne inorganic zinc silicate coating. When modifying the potassium silicate solution, styrene-acrylic emulsion and silane coupling agent are used to hybridize and modify the potassium silicate aqueous solution step by step, which can improve the stability of the coating. The viscosity of the hybridized and modified potassium silicate solution is moderate, and the waterborne inorganic zinc silicate coating prepared with Component B has good anti-settling performance. Component B is slowly added to Component A to prevent local powder aggregation. After mixing, there are no bubbles or particles, and the waterborne inorganic zinc silicate coating has good dispersibility and moderate viscosity, making it suitable for construction. Detailed Embodiments
[0037] In order to make the objectives, technical solutions and advantages of the present disclosure clearer, the present disclosure will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure, and are not used to limit the present disclosure.
[0038] Products and Reagents: Unless otherwise specified, the products used in the embodiments of this application are all from conventional commercially available products.
[0039] Raw material flaky zinc base material: The D50 particle size is 15 - 45 μm, and the zinc content is 96%. It is purchased from Hunan Xinweiling Metal New Materials Technology Co., Ltd. The modified acrylate emulsion is a modified epoxy acrylate: purchased from Risheng New Materials Co., Ltd., product name RV-1036; the acrylic acid modified polyurethane emulsion is an aliphatic acrylic acid modified polyurethane emulsion, purchased from Foshan Wengkel Trade Co., Ltd., model H351. Waterborne silicone resin, which is a methylphenyl silicone resin, brand Evonik, product name: P80 / X; Fatty alcohol polyoxyethylene ether, CAS No. 9004-95-9, purchased from Jiangsu Shengtai Chemical Technology Co., Ltd., product name alcohol ether AE0-9; Alkylphenol polyoxyethylene ether, purchased from Shandong Zibo Haijie Chemical Co., Ltd., product name NP(OP, TX)-10; Block polyether, which is a propylene glycol block polyether, purchased from Guangdong Zhongke Hongtai Co., Ltd., product name propylene glycol block polyether L-65; Polysiloxane surfactant, which is a polyether-modified polysiloxane, brand Evonik, product name 5840; Aqueous potassium silicate solution: M 2.5 - 3.9, potassium silicate content 45%, purchased from Shandong Hanwei Environmental Protection Technology Co., Ltd.
[0040] Testing Items and Methods The particle size of the flaky zinc-based material is detected according to GB / T 19077-2016 "Particle Size Analysis - Laser Diffraction Method"; The zinc content is detected according to GB / T 12689.12-2021 "Methods for Chemical Analysis of Zinc and Zinc Alloys"; The water surface spreading area is detected according to GB / T 3173-1882 "Determination of the Water-Covering Area of Aluminum Powder" and YST 617.10-2007 "Methods for Determining the Physical and Chemical Properties of Aluminum, Magnesium and Their Alloy Powders - Part 10: Determination of the Water-Covering Area of Aluminum Powder".
[0041] The coating thickness is detected according to ISO 2808:2019 "Paints and Varnishes - Determination of Film Thickness"; The pull-off adhesion is detected according to ASTM D4541-22 "Standard Test Method for Measuring Adhesion by Pull-Off Using a Portable Adhesion Tester"; The neutral salt spray resistance is detected according to ISO 9227:2022 "Corrosion Tests in Artificial Atmospheres - Salt Spray Tests".
[0042] Example 1 Preparation of Modified Flaky Zinc-Based Material for Waterborne Inorganic Zinc Silicate Coating Take 98 parts of raw flaky zinc-based material with a D50 particle size of 17μm and a zinc content of 96% and place them in a pre-stirring container. While stirring, spray and add 2 parts of a composite modifier with a weight ratio of polysiloxane surfactant: isocetyl alcohol: modified acrylate emulsion of 0.6:0.4:1.1 using a sprayer. The flow rate of the sprayer is 6 ml / min, and the volume flow rate of the spray gas is 10 ml / min. After adding, seal and continue stirring for 20 min until pre-mixed evenly to prepare a flaky zinc-based material coated with the composite modifier; Add 400 parts of glass beads with a diameter of 3 mm to a 10 L horizontal ball mill. Add the flaky zinc-based material coated with the composite modifier to the ball mill and mill it at a rotational speed of 170 r / min for 3 h. Remove the glass bead grinding media through a 40-mesh sieve to obtain a dry powder modified flaky zinc-based material.
[0043] Examples 2 - 3 The differences between Examples 2 - 3 and Example 1 lie in the different addition amounts of the raw flaky zinc-based material and the composite modifier. The different parts are shown in Table 1.
[0044] Table 1 In Examples 1-3, the weight ratio of the raw material flaky zinc base material to the composite modifier is 28:1 to 199:1.
[0045] The particle size, zinc content, and water surface spreading area of the modified flaky zinc base materials prepared in Examples 1-3 were tested, and compared with those of the raw material flaky zinc base materials. The results are shown in Table 2.
[0046] Table 2 As can be seen from Table 2, as the dosage of the composite modifier increases, the coating layer thickens, and the particle size increases slightly; the thickening of the coating layer leads to a decrease in the spreading area; when the dosage of the composite modifier decreases, the coating layer is relatively thin, and the zinc flakes are more easily broken after ball milling, resulting in a decrease in particle size; the spreading area of Example 3 decreases because the amount of the composite modifier is small, and there is a possibility of oxidation and caking on the zinc surface, leading to a decrease in the water surface spreading area.
[0047] The particle size of Example 1 is moderate (18.8 μm), the spreading area is the highest (1750 cm 2 / g), and the zinc content meets the standard (93.9%), with the best comprehensive performance.
[0048] Examples 4-5 The difference between Examples 4-5 and Example 1 is that the weights of the film-forming resin, surfactant, and cosolvent included in the composite modifier are different. The different parts are shown in Table 3.
[0049] Table 3 According to Examples 1-3, the particle size, zinc content, and water surface spreading area of the modified flaky zinc base materials prepared in Examples 4-5 were tested. The results are shown in Table 4.
[0050] Table 4 Detection Index Example 1 Example 4 Example 5 Particle Size D50 / μm 18.8 18.2 19.0 <![CDATA[Spreading area on water surface cm 2 / g]]> 1750 1650 1780 Zinc Content % 93.9 93.1 93.6 Compared with Example 1, in Example 4, the proportion of the modified acrylate emulsion decreases, the film-forming property weakens, the zinc flakes are more easily broken during ball milling, and D50 decreases to 18.2 μm; the proportion of the polysiloxane surfactant and 2-methyl-2,4-pentanediol increases, and the proportion of the modified acrylate emulsion decreases, resulting in a decrease in the dispersion stability compared with Example 1, and the spreading area decreases to 1650 cm 2 / g.
[0051] In Example 5, the proportion of the modified acrylate emulsion increases significantly, the coating layer thickens, buffering the impact of ball milling, and D50 increases to 19.0 μm. The significant increase in the proportion of the modified acrylate emulsion enhances the isolation effect between zinc flakes, significantly optimizing the dispersibility, and the spreading area increases to 1780 cm 2 / g.
[0052] Example 5 has excellent dispersibility and is suitable for scenarios with high shielding requirements; Example 4 reduces the dosage of the modified acrylate emulsion and is an economical choice.
[0053] Example Comparative Example 1 The difference between Example Comparative Example 1 and Example 5 is that the weight ratio of the polysiloxane surfactant: isohexylene glycol: modified acrylate emulsion is 0.2:0.2:0.7; Example Comparative Example 2 The difference between Example Comparative Example 1 and Example 5 is that the weight ratio of the polysiloxane surfactant: isohexylene glycol: modified acrylate emulsion is 1.2:1.2:2; The particle size, zinc content, and water surface spreading area of the modified flaky zinc base material prepared in Example Comparative Example 1 were tested, and the results are shown in Table 5.
[0054] Table 5 Detection Index Example 5 Example Comparative Example 1 Example Comparative Example 2 Particle Size D50 / μm 19.0 17.5 21.2 <![CDATA[Spreading area on the water surface cm 2 / g]]> 1780 Floating Fine Powder Agglomerates Fine Powder Bubbles Floating Zinc Content % 93.6 94.3 92.5 In Example Comparative Example 1, the modified acrylate emulsion only accounts for 0.7 parts, the coating layer is weak, and the zinc flakes are more likely to break during ball milling, resulting in a decrease in particle size. In Example Comparative Example 2, the total amount of the modifier reaches 4.4 parts, and excessive coating leads to particle adhesion and an increase in particle size.
[0055] In Example Comparative Example 1, the total amount of polysiloxane and isohexylene glycol is only 0.4 parts, the wetting of zinc powder is insufficient, the dispersibility is poor, and floating fine powder aggregates are formed. In Example Comparative Example 2, the modifier is excessive, the polysiloxane is added to 1.2 parts, the viscosity of the system increases, the fluidity of the zinc flakes decreases, and they suspend on the surface.
[0056] In Example Comparative Example 1, the proportion of the modified acrylate emulsion is low, the coating is incomplete, and the exposed zinc will quickly react with trace moisture / oxygen in the environment to form a dense ZnO passivation film, preventing further oxidation. The zinc oxidation is slight and the content slightly increases; compared with Example 5, although the complete coating layer blocks most of the oxidation medium, the modifier itself contains hydrophilic groups (such as -COOH in acrylate), which may introduce trace moisture, resulting in slow oxidation. In Example Comparative Example 2, the zinc content decreases because the total amount of the modifier is high, the increase in the modifier brings a dilution effect, and the excessive modifier may introduce moisture or impurities, and uneven local coating leads to zinc oxidation, thus resulting in a decrease in zinc content.
[0057] Example 6 The difference between Example 6 and Example 5 is that the composite modifier is the weight ratio of fatty alcohol polyoxyethylene ether: ethylene glycol amine: acrylic acid modified polyurethane emulsion is 0.4:0.4:1.7; 600 parts of glass beads are added to the ball mill; the flow rate of the sprayer is 3 ml / min, and the volume flow rate of the spray gas is 5 ml / min.
[0058] Example 7 Example 7 is different from Example 5 in that the composite modifier is alkylphenol polyoxyethylene ether: ethylene glycol amine: waterborne silicone resin with a weight ratio of 0.4:0.4:1.7; 800 parts of glass beads are added to the ball mill; the flow rate of the sprayer is 10 ml / min, and the volumetric flow rate of the spray gas is 15 ml / min.
[0059] Example 8 Example 8 is different from Example 5 in that the composite modifier is block polyether: isohexylene glycol: modified acrylate emulsion resin with a weight ratio of 0.4:0.4:1.7; 600 parts of glass beads are added to the ball mill; the flow rate of the sprayer is 8 ml / min, and the volumetric flow rate of the spray gas is 12 ml / min.
[0060] The particle size, zinc content, and water surface spreading area of the modified flaky zinc base materials prepared in Examples 6 to 8 were tested, and the results are shown in Table 6.
[0061] Table 6 From Table 6, in Example 8, the rigid silicone resin coating layer has a strong buffering effect during ball milling, reducing the zinc sheet crushing efficiency and resulting in relatively larger particle sizes; in Example 9, the wettability of the block polyether is better than that of the fatty alcohol polyoxyethylene ether in Example 7, improving the dispersion uniformity, and the particle size is close to that in Example 5; in Example 8, the zinc content is the lowest. Compared with other film-forming resins, the silicone resin has slightly worse coating uniformity, resulting in significant local oxidation, so the zinc content is relatively lower; in Example 9, the block polyether and the modified acrylate emulsion can synergistically inhibit zinc oxidation, resulting in a relatively higher zinc content; in Example 8, the silicone resin reduces the surface energy, making the zinc sheet more difficult to spread in the aqueous phase compared to other resins, so the water surface spreading area is slightly smaller; in Examples 7 and 9, the film-forming property of the acrylic-modified polyurethane is slightly inferior to the wettability of the modified acrylate emulsion, so the water surface spreading area is relatively smaller than that in Example 9.
[0062] Example 10 Example 10 is different from Example 5 in that the composite modifier is polysiloxane surfactant: isohexylene glycol: waterborne silicone resin: acrylic-modified polyurethane emulsion with a weight ratio of 0.4:0.4:0.5:1.2. The particle size, zinc content, and water surface spreading area of the modified flaky zinc base material prepared in Example 10 were tested, and the results are shown in Table 7.
[0063] Table 7 Detection Index Example 5 Example 10 Particle Size D50 / μm 19.0 18.3 <![CDATA[Spreading area on water surface cm 2 / g]]> 1780 1850 Zinc Content % 93.6 93.8 Example 10 introduced a modified silicone resin and a modified acrylic polyurethane emulsion. The silicone resin formed a denser coating layer, reducing the breakage and agglomeration of zinc flakes during the ball milling process. The acrylic-modified polyurethane emulsion reduced the viscosity and avoided particle adhesion. The two enhanced the toughness of the coating, and the prepared modified flaky zinc base material had a reduced particle size. The silicone significantly improved the surface wettability, making the zinc flakes easier to unfold in the aqueous phase. The dispersion stability of the acrylic-modified polyurethane was better than that of the acrylate, reducing the accumulation of zinc flakes, thereby increasing the spreading area on the water surface. When the proportion of the acrylic-modified polyurethane decreased, the dilution effect on zinc weakened. The antioxidant property of the silicone was better than that of the modified acrylate emulsion, further inhibiting the oxidation loss of zinc and increasing the zinc content.
[0064] Examples 11 - 13 The difference between Examples 11 - 13 and Example 10 was that the particle sizes of the raw material flaky zinc base materials were different, and the different parts are shown in Table 8.
[0065] Table 8 The particle sizes, zinc contents, and spreading areas on the water surface of the modified flaky zinc base materials prepared in Examples 11 - 13 were tested, and the results are shown in Table 9.
[0066] Table 9 Compared with Example 10, for Example 11, the particle size of the raw material flaky zinc base material increased, the ball milling crushing efficiency decreased relatively, and the spreading area decreased. For Example 12, the particle size further increased, and the large particles were more difficult to break, with a significant reduction in dispersibility. For Example 13, the particle size continued to increase, and the spreading area further decreased. The specific surface area of the large particle zinc decreased, the oxidation loss decreased, the ball milling time was the same, the degree of crushing decreased, the exposure of the fresh zinc surface decreased, and the zinc content increased slightly.
[0067] Application Example 1 Prepare a waterborne inorganic zinc silicate coating S1’: Prepare Coating A. Take 35 parts of potassium silicate aqueous solution (M is 3.9, content is 45%), add 1.5 parts of styrene-acrylic emulsion while stirring, and stir evenly. Dropwise add 1 part of silane coupling agent and stir evenly. Then add 0.5 part of dispersant and stir evenly. Then add 0.1 part of defoamer, 0.5 part of anti-settling agent, and 0.2 part of leveling agent, and stir and mix evenly. S2’: Prepare Coating B. Take 10 parts of the modified flaky zinc base material for the waterborne inorganic zinc silicate coating, 5 parts of barium sulfate, 30 parts of phosphorous iron powder, 5 parts of talc powder, 3 parts of mica powder, and 4 parts of potassium feldspar powder, and stir and mix evenly. S3’: Stir Coating A at low and medium speeds, and slowly add Coating B to Coating A. After adding, continue to stir at low and medium speeds until evenly mixed.
[0068] In Application Example 1, the modified flaky zinc base material used in Coating B is the modified flaky zinc base material prepared in Example 10.
[0069] Application Examples 2 - 3 The differences between Application Examples 2 - 3 and Application Example 1 are that the amounts of each component added to Coating A and Coating B are different, as shown in Table 10.
[0070] Table 10 Application Example 4 The difference between Application Example 4 and Application Example 2 is that M of the potassium silicate aqueous solution is 2.5.
[0071] Application Example 5 The difference between Application Example 5 and Application Example 2 is that M of the potassium silicate aqueous solution is 3.2.
[0072] Application Comparative Example 1 The difference between Application Comparative Example 1 and Application Example 2 is that the styrene-acrylic emulsion is replaced with an equal amount of silane coupling agent in Coating A.
[0073] Application Comparative Example 2 The difference between Application Comparative Example 2 and Application Example 2 is that the silane coupling agent is replaced with an equal amount of styrene-acrylic emulsion in Coating A.
[0074] Application Comparative Example 3 The difference between Application Comparative Example 3 and Application Example 2 is that neither the silane coupling agent nor the styrene-acrylic emulsion is added to Coating A.
[0075] Application Comparative Example 4 The difference between Application Comparative Example 4 and Application Example 2 is that the raw material flaky zinc base material is directly used in Coating B.
[0076] Application Comparative Example 5 The difference between Application Comparative Example 5 and Application Example 2 is that only the modified flaky zinc base material is added to Coating B, and no other fillers are added.
[0077] Application Comparative Example 6 The difference between Application Comparative Example 6 and Application Example 2 is that Coating A and Coating B are not distinguished, and all components are stirred and mixed evenly at low and medium speeds together.
[0078] Application Comparative Example 7 The difference between Application Comparative Example 7 and Application Example 2 is that the modified flaky zinc base material prepared in Application Comparative Example 2 is used in Coating B.
[0079] The dispersion performance of the waterborne inorganic zinc silicate coatings prepared in Application Examples 1 - 3 and Application Comparative Examples 1 - 7 was tested, and the results are shown in Table 11.
[0080] Table 11 Application Example Dispersion Time (min) Surface Floating Matter Residue (%) Application Example 1 12 None 0 Application Example 2 10 None 0 Application Example 3 15 None 0 Application Example 4 15 None 0 Application Example 5 12 None 0 Application Example Comparative Example 1 18 Fine Powder Bubbles 4~5 Application Example Comparative Example 2 14 Trace Floating 1~2 Application Example Comparative Example 3 25 Massive Agglomeration 8~10 Application Example Comparative Example 4 20 Fine Powder Bubbles 6~8 Application Example Comparative Example 5 8 None 0 Application Example Comparative Example 6 30 Gel Blocks 15 Application Example Comparative Example 7 18 Small Amount of Fine Powder Bubbles 4~5 In Application Examples 1 - 3 of Table 11, as the filler of Coating B increases, the dispersibility decreases. The filler (such as talcum powder) has a high oil absorption capacity, which can increase the viscosity of the system. In Application Examples 4 - 5, as the modulus of potassium silicate decreases, the dispersion time increases. Potassium silicate M2.5 is lower (more short-chain molecules) than M3.9, with a small solution viscosity and poor suspension ability for the filler / zinc powder. The dispersion time needs to be extended to avoid sedimentation; the polymerization degree of potassium silicate M3.2 has slightly better dispersibility than that of the M2.5 modulus; the polymerization degree of potassium silicate M3.9 has the best dispersibility compared to M2.5 and M3.9.
[0081] In the comparative example 1 of the application example, the silane coupling agent completely replaces the styrene-acrylic emulsion, lacking a film-forming substance and having poor wettability of zinc powder, resulting in the modifier being unable to be effectively adsorbed on the surface of zinc powder, forming undissolved "fine powder bubbles". In the comparative example 3 of the application example, there is no organic modifier at all, and the surface of zinc powder is not wetted and directly agglomerates into blocks; in the comparative example 2 of the application example, the absence of the silane coupling agent makes it impossible for zinc powder and potassium silicate solution to form a chemical bond. Zinc powder only relies on physical mixing and can float with slight stirring.
[0082] In the comparative example 4 of the application example, unmodified raw material flake zinc powder is used. Unmodified zinc powder is prone to agglomeration and has poor wetting performance.
[0083] In the comparative example 5 of the application example (without filler), the dispersibility is excellent, but the mechanical properties and anti-corrosion properties of the coating are poor. See Table 10 for the coating thickness, pull-off adhesion, and neutral salt spray resistance performance.
[0084] In the comparative example 6 of the application example (full-component mixing), potassium silicate reacts with zinc powder in advance to form insoluble substances, resulting in gel and residue, indicating the necessity of step-by-step mixing.
[0085] In the comparative example 7 of the application example, the composite modifier is excessive, which may cause partial agglomeration, reduce the material transfer efficiency during spraying, and slightly reduce the coating thickness.
[0086] The waterborne inorganic zinc silicate coatings prepared in Application Examples 1 - 3 and Comparative Examples 1 - 7 of the application example are filtered through an 80-mesh sieve and then spray-coated. The coating thickness, pull-off adhesion, and neutral salt spray resistance performance are measured, and the results are shown in Table 12.
[0087] Table 12 From Table 12, for the coating thickness performance of Application Examples 1 to 3, in Application Example 3, due to the high solid content, the film thickness increased significantly after spraying; in Application Example 1, the film thickness was the thinnest, suitable for the requirement of thin coating. For the adhesion performance, in Application Example 1, due to the more continuous film formation of potassium silicate under low filler content, the adhesion was the best; in Application Example 3, the adhesion decreased because the increase in filler weakened the chemical bonding between the coating and the substrate. For the salt spray resistance performance, Preparation Example 2 showed the best performance, as the zinc-based material provided balanced cathodic protection; potassium silicate and the filler formed a dense shielding layer; in Preparation Example 3, the salt spray resistance performance decreased slightly because the excessive addition of the zinc-based material led to an increase in the porosity of the coating.
[0088] For Application Examples 2 and Application Examples 4 to 5, as the modulus of potassium silicate decreased, the coating thickness increased, the adhesion decreased, and the salt spray resistance decreased. The solid content of potassium silicate with a modulus of M2.5 was relatively low compared to M3.2 and M3.9. More paint was required to reach the same film thickness, and the thickness increased slightly after spraying, but the uniformity might decrease; the short-chain molecules of M2.5 potassium silicate reacted weakly with the substrate, and the shrinkage rate was large after film formation, resulting in a decrease in adhesion; the number of long-chain molecules of M3.2 increased, improving the interfacial bonding, but it was still lower than that of the M3.9 modulus; the film density of low-modulus potassium silicate was poor, and the corrosive medium was easy to penetrate, resulting in a decrease in salt spray resistance; as the modulus increased, the film layer defects decreased, and the corrosion resistance improved.
[0089] In Application Example Comparative Examples 1 to 3, the adhesion of the coating decreased significantly. Due to the synergistic effect of styrene-acrylic emulsion and silane coupling agent, in Application Example Comparative Example 2, the styrene-acrylic emulsion provided flexible film formation, and the silane coupling agent enhanced the interfacial bonding. Neither of them could be missing.
[0090] The salt spray resistance of Application Example Comparative Example 4 (unmodified zinc) was only 900 h. The uncoated zinc oxidized rapidly and lost its cathodic protection ability. Therefore, it was necessary to use a modified flaky zinc-based material.
[0091] The salt spray resistance of Application Example Comparative Example 5 (without filler) decreased, indicating that barium sulfate, mica powder, etc. had a physical barrier effect on the corrosive medium and could improve the salt spray resistance. The filler in Coating B had a physical shielding effect on the coating.
[0092] In Application Comparative Example 6, full-component mixing was used, and the coating performance was poor. In the case of full-component mixing, potassium silicate reacted directly with zinc powder to form a gel, resulting in a porous coating.
[0093] In Application Comparative Example 7, the composite modifier was excessive, which might lead to partial agglomeration, reducing the material transfer efficiency during spraying and decreasing the coating thickness.
[0094] The above has introduced this application in detail. Specific examples are used in this application to elaborate on the principle and implementation manner of this application. The description of the above embodiments is only used to help understand this disclosure and the core idea. It should be noted that for those of ordinary skill in the art in this technical field, without departing from the principle of this application, several improvements and modifications can still be made to this application, and these improvements and modifications also fall within the protection scope of the claims of this application.
Claims
1. A modified flaky zinc base material for waterborne inorganic zinc silicate coatings, characterized in that, The modified flaky zinc base material comprises the following raw material components by weight: 96.5 - 99.5 parts of raw flaky zinc base material; 0.5 - 3.5 parts of a composite modifier; the modified flaky zinc base material is obtained by coating and modifying the raw flaky zinc base material with the composite modifier and then performing ball milling treatment.
2. The modified flaky zinc base material according to claim 1, wherein The particle size D50 of the raw flaky zinc base material is 15 - 45 μm; the composite modifier includes a film-forming resin, a surfactant, and a cosolvent; the weight ratio of the film-forming resin: surfactant: cosolvent is (1 - 1.7):(0.4 - 1):(0.4 - 1).
3. The modified flaky zinc-based material according to claim 2, wherein, The film-forming resin includes at least one of a modified acrylate emulsion, an acrylic acid-modified polyurethane emulsion, and an aqueous organosilicon resin; the surfactant includes at least one of a nonionic surfactant and a silicon-modified surfactant; the cosolvent includes at least one of isohexylene glycol and ethylene glycol amine.
4. The modified flaky zinc base material according to claim 3, wherein, The nonionic surfactant includes at least one of a fatty alcohol polyoxyethylene ether, an alkylphenol polyoxyethylene ether, and a block polyether; the silicon-modified surfactant includes a polysiloxane surfactant. A method for preparing the modified flaky zinc base material as claimed in claim 1, characterized by comprising the following steps: S1: Take 96.5 - 99.5 parts of the raw flaky zinc base material and place it in a pre-stirring container, and while stirring, spray and add 0.5 - 3.5 parts of the composite modifier with a sprayer until pre-mixed evenly. S2: Take 400 - 800 parts of glass beads and add them to a ball mill, add the material prepared in S1 to the ball mill, perform ball milling and mix evenly; screen the glass beads to obtain the modified flaky zinc base material.
5. The preparation method of the modified flaky zinc-based material according to claim 5, characterized in that, In S1, the liquid flow rate of the sprayer is 3 - 10 ml / min; the gas volume flow rate of the spray gas is 5 - 15 L / min.
6. An aqueous inorganic zinc silicate coating, characterized in that, The waterborne inorganic zinc silicate coating includes coating A and coating B. Coating A comprises 35 - 55 parts of an aqueous potassium silicate solution, 1.5 - 3 parts of a styrene-acrylic emulsion, 1 - 2 parts of a silane coupling agent, 0.5 - 2.0 parts of a dispersant, 0.1 - 0.3 parts of an antifoaming agent, 0.5 - 1.5 parts of an anti-settling agent, and 0.2 - 0.5 parts of a leveling agent by weight; Coating B comprises 10 - 40 parts of the flaky zinc base material for the waterborne inorganic zinc silicate coating as described in any one of claims 1 - 4 or the flaky zinc base material for the waterborne inorganic zinc silicate coating prepared by the preparation method described in any one of claims 5 - 6, 5 - 15 parts of barium sulfate, 3 - 10 parts of phosphorus iron powder, 5 - 10 parts of talc powder, 3 - 8 parts of mica powder, and 4 - 10 parts of potassium feldspar powder by weight.
7. A method for preparing the waterborne inorganic zinc silicate coating according to claim 7, characterized in that, The preparation method of the waterborne inorganic zinc silicate coating includes the following steps: S1': Prepare coating A. Take 35 - 55 parts of the aqueous potassium silicate solution, and while stirring, add 1.5 - 3 parts of the styrene-acrylic emulsion and stir evenly; dropwise add 1 - 2 parts of the silane coupling agent and stir evenly; then add 0.5 - 2.0 parts of the dispersant and stir evenly; then add 0.1 - 0.3 parts of the antifoaming agent, 0.5 - 1.5 parts of the anti-settling agent, and 0.2 - 0.5 parts of the leveling agent, and stir and mix evenly. S2’: Prepare Coating B. Take 10 - 40 parts of modified flaky zinc base material for waterborne inorganic zinc silicate coating, 5 - 15 parts of barium sulfate, 3 - 10 parts of ferrophosphorus powder, 5 - 10 parts of talc powder, 3 - 8 parts of mica powder, and 4 - 10 parts of potassium feldspar powder, and stir and mix them evenly; S3’: Stir Coating A at low to medium speed, slowly add Coating B to Coating A, and continue to stir at medium to low speed until evenly mixed after adding.
Citation Information
Patent Citations
A flake-type epoxy olefin-zinc primer and its preparation method
CN111253827B
A water-based inorganic zinc-rich coating and its preparation method
CN112143269B
A composite anti-settling agent for alcohol-soluble inorganic zinc silicate paint and its preparation method, zinc powder components of inorganic zinc silicate paint and their preparation method
CN113897091B
A water-based zinc-rich anticorrosive coating that resists the spread of corrosion and a preparation method thereof
CN116200096B
Cited By
Modified flaky zinc powder, modification method, anticorrosive paint and preparation method of anticorrosive paint
CN122274164A